Morphological variation between two fish populations – phenotypic radiation in a rare case of geographical isolation - Fernanda Biscaino Saluceste; Fábio Teruo Mise; Bruna Angelina Mayer; Franciele Fernanda Kerniske; Roberto Ferreira Artoni; Jean Ricardo Simões Vitule; Letícia Cucolo Karling; Igor de Paiva Affonso (Acta Limnologica Brasiliensia)
Abstract Aim We examined the morphology of two populations of the Neotropical Characidae Psalidodon aff. fasciatus from two distinct environments with different selective pressures. One is the single fish population from an isolated lake, hence is deprived of interaction with any other fish species for countless generations. The other shares life-history with several fish. Methods We obtained 10 linear body measurements from 294 specimens from both populations, calculated and compared the ecomorphological indices for each population. Results We found significant distinct morphometry between populations, primarily attributed to the high level of isolation observed in individuals from the isolated population. This population exhibited greater morphological variation, likely due to reduced selection pressure and limited ecological interactions (e.g., absence of other fish species). Conversely, the non-isolated population displayed less morphological variation, possibly as a result of more intense intra- or interspecific interactions, such as competition and predation. Conclusions Considering that allopatry and major factors such as “isolation time” and “ecological interactions” are crucial drivers of evolution, this study highlights a rare case of natural isolation and provides insights for evolutionary investigations on isolated populations, allopatric speciation, and the role of ecological interactions in phenotypic intrapopulation variation.